Membangun Integritas dalam Profesi Pendidik: Etika, Tanggung Jawab, dan Akuntabilitas - Pangaribuan, Tumewa; Harianja, Sri Indriani; Nurjannah, Intan; Rahayani, Fitri; Nurhaliza, Adhwa (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research is to explore the role of integrity in the teaching profession and its impact on the quality of education. This research uses the literature study method. The literature study was carried out by conducting a comprehensive and systematic search through academic databases such as PubMed, Google Scholar, and educational journal databases to identify literature that is relevant to integrity in the teaching profession. Keywords used include "educator integrity", "educational ethics", "educational quality", and the like. The research results show that the integrity of educators plays a crucial role in shaping the overall quality of education. Teachers who maintain their integrity create trust and credibility among students, parents, and colleagues, facilitate positive learning, and encourage student character and moral development. Integrity also helps maintain high standards of professionalism in the teaching profession and overcome injustice and discrimination in education.